1971
DOI: 10.1172/jci106601
|View full text |Cite
|
Sign up to set email alerts
|

Role of gastrin supersensitivity in the pathogenesis of lower esophageal sphincter hypertension in achalasia

Abstract: A B STRA CT Intraluminal manometric studies were carried out in 19 patients with untreated achalasia and in 20 normals. Lower esophageal sphincter (LES) pressure was 50.5 ±4.6 mm Hg in patients with achalasia as compared with 19.4 ±1.3 mm Hg in the normal group.In both groups, the LES pressure was lowered when exogenous 0.1 N HCl was placed into the stomach. Although the nadir of pressure attained with acid suppression was the same, the per cent inhibition was significantly greater in patients with achalasia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
6

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 20 publications
2
36
0
6
Order By: Relevance
“…Consequently lower esophageal sphincter pressure is frequently increased in idiopathic achalasia [14][15][16][17] and frequently decreased in Chagas' disease [16][17][18][19] which may explain the variation in the lower esophageal sphincter pressure [20] , and the heterogeneity seen in these patients [21] .…”
Section: Differences Between Idiopathic and Chagas' Disease Achalasiamentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently lower esophageal sphincter pressure is frequently increased in idiopathic achalasia [14][15][16][17] and frequently decreased in Chagas' disease [16][17][18][19] which may explain the variation in the lower esophageal sphincter pressure [20] , and the heterogeneity seen in these patients [21] .…”
Section: Differences Between Idiopathic and Chagas' Disease Achalasiamentioning
confidence: 99%
“…Previous studies have reported differences in esophageal response to gastrin [14,15,18] and to atropine [15,22] . These mechanisms have not been completely elucidated in Chagas' disease [11,13] [ Table 1].…”
Section: Differences Between Idiopathic and Chagas' Disease Achalasiamentioning
confidence: 99%
“…If circulating gastrin is not responsible for the genesis of LESP, then an alternative mechanism of inhibitory effect of such hormone must be considered. (b) Defects in gastrin release and gastrin sensitivity have been proposed as the basis of LES incompetence (10,11) and LES hypertension in achalasia (11)(12)(13), respectively. If gastrin is not a major determinant of LESP, then concepts about the pathogenesis of LES disorders need to be revised, and alternative pathogenetic mechanisms must be investigated to provide a basis for rational therapy.…”
Section: Genesis Of Basal Lower Esophageal Sphincter Pressurementioning
confidence: 99%
“…Some observers have proposed that circulating gastrin (3,4) is the major determinant of LESP. This hypothesis of gastrin closure of lower esophageal sphincter (LES) has been used as a model: (a) to explain the pathogenesis of a variety of disorders of the LES such as sphincter incompetence in reflux esophagitis (9)(10)(11) and sphincter hypertension in achalasia (11,12); (b) to explain the mechanism of inhibitory action of secretin (3) and cholecystokinin (13) on LESP; and (c) to estimate endogenous gastrin activity in vivo (14). On the other hand, others (5-7) have recently questioned some of the evidence which formed the basis of the hypothesis that gastrin has a major role in the physiological regulation of LESP.…”
Section: Introductionmentioning
confidence: 99%
“…1 Abbreviations used in this paper: CCK-PZ, cholecystocompetence at the gastroesophageal junction in man (1)(2)(3)(4)(5). Recent studies have focused on the neural (6, 7) and humoral (8)(9)(10)(11) factors that augment LES pressure above its resting level. However, the genesis of the resting LES strength itself is not known.…”
mentioning
confidence: 99%